2018
DOI: 10.3390/ijms19123787
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Colorectal Cancer by Dietary Compounds

Abstract: Colorectal cancer is one of the leading causes of death, and the third most diagnosed type of cancer, worldwide. It is most common amongst men and women over 50 years old. Risk factors include smoking, alcohol, diet, physical inactivity, genetics, alterations in gut microbiota, and associated pathologies (diabetes, obesity, chronic inflammatory bowel diseases). This review will discuss, in detail, the chemopreventive properties of some dietary compounds (phenolic compounds, carotenoids, iridoids, nitrogen comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 273 publications
(302 reference statements)
1
59
0
1
Order By: Relevance
“…These results, which were in line with the microscopic considerations, suggested that attempted transitions from mesenchymal to neuronal lineage occurred in the GBM cells exposed to crocetin treatment. Different independent studies showed the capacity of crocetin to induce cancer cell differentiation through the inhibition of particular factors involved in the regulation of gene expression, such as HDACs [33,34]. Indeed, these proteins are important players in the onset and maintenance of tumors due to their inhibitory effects on the expression of suppressor genes in neoplastic disease.…”
Section: Discussionmentioning
confidence: 99%
“…These results, which were in line with the microscopic considerations, suggested that attempted transitions from mesenchymal to neuronal lineage occurred in the GBM cells exposed to crocetin treatment. Different independent studies showed the capacity of crocetin to induce cancer cell differentiation through the inhibition of particular factors involved in the regulation of gene expression, such as HDACs [33,34]. Indeed, these proteins are important players in the onset and maintenance of tumors due to their inhibitory effects on the expression of suppressor genes in neoplastic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of carotenoids, mainly β-carotene and lycopene, on a range of cancer biomarkers have been reported. These include those for lung cancer [22,23], colon cancer [24] and breast cancer [25,26].…”
Section: Cancermentioning
confidence: 99%
“…The anticancer potential and chemoprevention of polyphenols for cancer is a very innovative topic in the field of food, nutrition, and health, and have been recently reviewed by several authors [76][77][78]. Preliminary studies in different animal models, human epidemiological trials, and cell lines indicate a correlation between polyphenolic intake an prevention of a particular cancer, showing a decreased risk for different types of cancer or diminished recurrence of cancer after the consumption of flavonoids, especially in the case of CRC [77][78][79]. In Table 1, we observe most relevant studies on the action of polyphenols in connection to CRC.…”
Section: Direct and Gut-microbiota-modulating Mechanisms Of Action Ofmentioning
confidence: 99%